Managerial strategies and effective staff meetings in Nigerian Universities - Yusuf, Musibau Adeoye (Indonesian Journal of Educational Management and Leadership, 2023)
The study examined the leadership behaviour towards conducting effective staff meetings.in Oyo State Public Universities; investigated the various management strategies that have been adopted by the Heads of Department in ensuring effectiveness in staff meetings in public universities as well as assessed the effective management strategy with a view to improving staff meetings in public universities in Osun State. A descriptive survey research design was used for the study. The population for the study comprised the Heads of Departments and Academic staff members in all the public universities in Osun state. Two self-designed instruments were used, namely: Management Strategies and Staff Meetings in Universities Interview Guide (MSSMUIG) and Staff Meeting Questionnaire (SMQ) to elicit information from the respondents. Data collected were analysed using descriptive and content analysis. Frequency counts, percentages, means, and standard deviation were used to answer the research questions raised. Content analysis was used for the qualitative aspect. The results showed that all the management strategies adopted facilitates and enhances effective staff meetings in public universities in Osun State. It was further revealed that communication strategy was adopted because it afforded the staff members ample opportunities to express themselves and partake actively in decision-making process concerning departmental affairs as well as their personal affairs.. The study therefore, concluded that communication and management strategies were the most effective for staff meeting as they afforded members ample opportunities for expression and active participation in decision-making processes.